2014
DOI: 10.7717/peerj.646
|View full text |Cite
|
Sign up to set email alerts
|

Study of the effect on shelter cat intakes and euthanasia from a shelter neuter return project of 10,080 cats from March 2010 to June 2014

Abstract: Cat impoundments were increasing at the municipal San Jose animal shelter in 2009, despite long-term successful low cost sterilization programs and attempts to lower the euthanasia rate of treatable-rehabilitatable impounds beginning in 2008. San Jose Animal Care and Services implemented a new strategy designed to control overall feral cat reproduction by altering and returning feral cats entering the shelter system, rather than euthanizing the cats. The purpose of this case study was to determine how the prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 7 publications
9
45
0
Order By: Relevance
“…Low cost and free desexing programs targeted to locations and breeds contributing to high intake have been a major focus in the USA, and although conflicting results are reported, there is some evidence these programs decrease intake and numbers euthanized [ 27 , 37 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. These strategies reduce both owner-surrendered [ 49 ] and stray (i.e., owned dogs that became lost) intake [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low cost and free desexing programs targeted to locations and breeds contributing to high intake have been a major focus in the USA, and although conflicting results are reported, there is some evidence these programs decrease intake and numbers euthanized [ 27 , 37 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. These strategies reduce both owner-surrendered [ 49 ] and stray (i.e., owned dogs that became lost) intake [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found significant declines in shelter intakes of cats occurred when subsidized desexing or trap neuter return programs were implemented [ 39 , 40 ], but the effectiveness of subsidized desexing programs has had a variable impact on shelter intake of dogs. A study conducted in 2011 in San Jose, California identified Chihuahuas as a significant contributor to shelter intake, and implemented a free desexing program targeted at Chihuahuas and Chihuahua crosses [ 40 ]. As a result, overall dog admissions decreased from seven dogs per 1000 humans to 6.1 in two years [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in 2011 in San Jose, California identified Chihuahuas as a significant contributor to shelter intake, and implemented a free desexing program targeted at Chihuahuas and Chihuahua crosses [ 40 ]. As a result, overall dog admissions decreased from seven dogs per 1000 humans to 6.1 in two years [ 40 ]. Similarly, a free desexing program in Austin, Texas targeted to zip codes with high shelter intake, low average income and scarcity of veterinary facilities slowed the increase in dog admissions, compared to intakes from other zip codes [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is necessary to modify the strategy to sterilize more cats within the limited budget. Several countries have modified the TNR strategy to focus on specific areas with larger feline populations, and implemented intensive sterilization with the goal of expanding TNR programs into surrounding areas (Nutter, 2006;Mendes-de Almeida et al, 2011;Johnson & Cicirelli, 2014;Spehar & Wolf, 2018;Zito et al, 2018). This targeted, high-impact TNR intervention is more effective than sporadic TNR in reducing the community cat population (Kortis, 2014;Levy, Isaza & Scott, 2014;Kilgour et al, 2017).…”
Section: Introductionmentioning
confidence: 99%